2019
DOI: 10.18502/rmm.v7i1.5258
|View full text |Cite
|
Sign up to set email alerts
|

TEM Gene Detection in Clinical Pseudomonas aeruginosa and Escherichia coli Samples

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…In our study, amplicon sequencing of bla CTX-M revealed the predominance of bla CTX-M-15 (5/6, 83%) among the CTX-resistant E. coli isolates. These findings are in line with the fact that bla CTX-M-15 is the most widely spread ESBL genotype globally [ 34 ]. The emergence of bla CTX-M-15 has been attributed to the clonal spread of the E. coli O25b:H4-ST131 pandemic clone.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, amplicon sequencing of bla CTX-M revealed the predominance of bla CTX-M-15 (5/6, 83%) among the CTX-resistant E. coli isolates. These findings are in line with the fact that bla CTX-M-15 is the most widely spread ESBL genotype globally [ 34 ]. The emergence of bla CTX-M-15 has been attributed to the clonal spread of the E. coli O25b:H4-ST131 pandemic clone.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, amplicon sequencing of blaCTX-M revealed the predominance of blaCTX-M-15 (5/6, 83%) among the CTX-resistant E. coli isolates. These findings are in line with the fact that blaCTX-M-15 is the most widely spread ESBL genotype globally [32]. The emergence of blaCTX-M-15 has been attributed to the clonal spread of the E. coli O25b:H4-ST131 pandemic clone.…”
Section: Discussionsupporting
confidence: 79%